The impact of Malaysian Ringgit fluctuation towards profitabilityof Islamic Banks in Malaysia / Suhaily Maizan Abdul Manaf - Abdul Manaf, Suhaily Maizan (UiTM Cawangan Johor, 2019)
Profitability of a bank mostly relies on its financial performance as the ability to leverage operational, investment decisions and strategies to achieve a business financial constancy. This study is devoted to examine the selected Malaysian Ringgit factors that bring impact to the profitability of local Islamic banks in Malaysia. A set of data were obtained from each bank's financial statement and the World Bank data from year 2007 until 2016. Return on assets has been used as a dependent variable while debt to equity ratio, capital adequacy ratio, exchange rate and interest rate serve as an independent variable. The findings show that three independent variables give positive significant relationship and will be discussed further throughout the paper. For that purpose, policymakers should focus on these three variables for standardizing the economic environment to all local Islamic banks operating in this country.